A sensitivity study of the LIdar-Radiometer Inversion Code (LIRIC) using selected cases from Thessaloniki, Greece database. Issue 2 (17th January 2018) - Filioglou, M.; Siomos, N.; Poupkou, A.; Dimopoulos, S.; Chaikovsky, A.; Balis, D.
ABSTRACT: We investigate the uncertainty introduced to the optical and microphysical properties estimated with the lidar radiometer inversion code (LIRIC) by user-defined input parameters based on measurements carried out with a multi-wavelength Raman lidar and a sun photometer located at Thessaloniki, Greece (40.6° N, 22.9° E, 60 m above sea level). The sensitivity study involves three tests. We first evaluate the selection of the regularization parameters needed for the algorithm to initialize the iteration process. The latter two tests consider the impact of the boundary limits at the top/bottom (upper/lower limit) of the signal to the derived concentration profiles. The aforementioned tests were applied to two different cases, a Saharan dust event and a continental pollution case. We concluded that the largest uncertainties are introduced when varying the lower limit (more than 35%) regardless of the aerosol type or mode (fine/coarse). Varying the regularization parameters resulted in an uncertainty of 20%, and the selection of upper limit led to discrepancies of less than 3%. In conclusion, this sensitivity study indicates that future LIRIC users should apply an overlap function to the lidar signals before applying the methodology for minimizing the uncertainties in the near range.